La légitimité des littératures francophones
This paper intends to question the conditions and strategies of access to legitimacy and acknowledgement by contemporary peripheral Francophone writers who publish in Paris about their own different realities. Moreover, we will survey some questions raised by the use of Francophone fictional texts in the context of French Foreign Language teaching-learning process.